Conflict Resolution Model: Strategies for Handling Verbal Violence in High School Students in Majene Regency - Hasbahuddin Hasbahuddin; Uhwah Hasanah; Evy Segarawaty Ampry; Nur Fadhilah Umar (Bulletin of Counseling and Psychotherapy, 2026)
Verbal violence among high school students has become a significant problem in the educational environment, affecting students' mental health, academic performance, and social relationships. This study aims to develop a conflict resolution model for addressing verbal violence among high school students in Majene Regency. Verbal violence remains a prevalent issue in school environments, often manifested through ridicule, insults, threats, and discriminatory remarks based on ethnicity, religion, race, and intergroup relations. This study employed a research and development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through observations, interviews, and documentation involving students, teachers, and guidance and counseling practitioners. The developed model integrates peer mediation, restorative justice, and collaborative negotiation to promote constructive conflict resolution. The validation results indicate that the model is both theoretically sound and practically feasible for implementation in schools. The findings suggest that the model contributes to reducing verbal violence, improving students’ social interactions, and fostering a more inclusive school climate. Therefore, this model can serve as an alternative approach for guidance and counseling services in addressing verbal violence in educational settings.